2018
DOI: 10.14710/ijred.7.1.53-58
|View full text |Cite
|
Sign up to set email alerts
|

Scale up sediment microbial fuel cell for powering Led lighting

Abstract: Sediment microbial fuel cells (SMFCs) are expected to be utilized as a sustainable power source for remote environmental observing 30 day’s investigations of experiment to understand the long-term performance of SMFCs. The point of this investigation is to increase power generation, 8 individual sediment microbial fuel cells is stacked together either in series or in hybrid connection. Two combinations, of the hybrid connection, are proving to be the more effective one, step-up both the voltage and current of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For example, materials made from carbon cloth, carbon paper, carbon felt [79], graphite granules, carbon mesh [80], platinum, platinum black and activated carbon with single or tubular or multi-electrode configurations are suitable as electrodes [81]. These electrodes should have properties which render them biocompatible and stable In addition high electrical conductivity, and large surface area is recommended [82,83]. The cathode can be exposed to air or other additional electron acceptors like permanganate, chromium hexacyanoferrate and azo dye, etc.…”
Section: Microbial Fuel Cells For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, materials made from carbon cloth, carbon paper, carbon felt [79], graphite granules, carbon mesh [80], platinum, platinum black and activated carbon with single or tubular or multi-electrode configurations are suitable as electrodes [81]. These electrodes should have properties which render them biocompatible and stable In addition high electrical conductivity, and large surface area is recommended [82,83]. The cathode can be exposed to air or other additional electron acceptors like permanganate, chromium hexacyanoferrate and azo dye, etc.…”
Section: Microbial Fuel Cells For Wastewater Treatmentmentioning
confidence: 99%
“…The amount of electricity produced in this study, while low (26 mW/m2), was considerably higher than previously obtained with other wastewater types. Research conducted prior to 2004 had shown that organic and inorganic matter in marine sediments could be used in a novel type MFC design [82], making it apparent that a wide variety of substrates, materials and system architectures could be used to generate electricity from organic content with bacterial biomass. Still, power levels in all these applications were relatively low.…”
Section: Microbial Fuel Cells For Wastewater Treatmentmentioning
confidence: 99%
“…Voltage generation from SMFC is very low for powering small devices like wireless sensors and led lighting. SMFC voltage can be increased by the combination of series and parallel connections, but this method requires a large number of SMFC, 14 which requires the large area. When the load (1 kΩ) is added directly to SMFC, the voltage of SMFC starts to fall rapidly as the internal resistance of the SMFC is too large.…”
Section: Operation Of Dc-dc Boost Converter and Voltage Regulationmentioning
confidence: 99%
“…A sensor requires the voltage range of 2.5 to 5.0 V. There is a clear gap between the voltage generated by SMFC and voltage required by the sensor. In order to achieve the power required by a sensor, the parallel and series connection of MFC were made to increase the output voltage (about 3 V) and consequently the power, to supply small sensors and LED lighting . This method of increasing the voltage requires the large area and also voltage fluctuates with time.…”
Section: Introductionmentioning
confidence: 99%
“…However, PMFC cannot totally substitute the commercial use of fossil energy because the amount of energy produced is relatively low to support human life. This is because the rate of electron transfer from microorganisms to the electrode surface is still slow, where the conductivity and chemical content contained in the soil or mud acts as a planting medium that influences the rate of electron transfer (Aghababaie et al, 2015;Prasad and Tripathi, 2018).…”
Section: Introductionmentioning
confidence: 99%